The Accuracy of Satellite Derived Bathymetry in Coastal and Shallow Water Zone (International Journal of Built Environment and Sustainability, 2021)
Precise and accurate bathymetric measurements are conventionally acquired by means of ship-based acoustic equipment. Nevertheless, recent multispectral satellite imagery has been utilised as a substitute source to map the seabed topography which indicates new revolution in hydrographic surveying. This study assesses the satellite bathymetric depth’s accuracy based on the vertical uncertainty as stated in the Standards for Hydrographic Surveys issued by the International Hydrographic Organization. Two empirical algorithms, namely, Dierssen’s and Stumpf’s approaches have been adopted to model the seafloor topography over the coastal and shallow water at Tanjung Kupang, Malaysia. The outcomes demonstrate a decent correlation between the derived water depths and the sounding values acquired from a ship-based acoustic survey. For instance, a total of 1,215 out of the 1,367 generated water depths by Stumpf’s model have hit the minimum standard of survey in S-44. Similarly, out of the 1,367 samples from Diessen’s model, 1,211 samples have met the minimum requirement listed in the survey standard. The results demonstrate both imageries derived bathymetry models convey promising results which can be ultilised for bathymetric mapping application. Therefore, this imagery derived bathymetry can be considered as an alternative bathymetric surveying technique to supply cost-effective solution and survey data to support the Blue Economy and Sustainable Development Goals 14.
Keywords: Imagery derived bathymetry; Multispectral images; Bathymetric surveying